Defending the Defenders: Unveiling the Struggles of Legal Aid for Journalists in Indonesia - Permana, Eka Surya (Indonesia Media Law Review, 2024)
This paper sheds light on the challenges faced by legal aid in supporting journalists in Indonesia, exposing the daunting obstacles encountered by those who defend the defenders of truth. Through a comprehensive examination of legal cases, interviews with legal practitioners, and analysis of the socio-legal context, this paper uncovers the harsh realities confronting journalists as they navigate complex legal landscapes. It reveals a narrative of resource scarcity, threats to personal safety, and a pervasive lack of awareness regarding journalists' rights, all of which exacerbate the vulnerability of media professionals. Furthermore, entrenched legal frameworks often impede rather than facilitate press freedom, complicating the pursuit of justice. This paper underscores the urgent need for increased resources, improved legal training, and systemic reforms to strengthen legal aid for journalists in Indonesia. It calls for concerted efforts among stakeholders to champion the cause of press freedom and defend the defenders of truth in Indonesia's media environment.